Measuring the dimensionality of human resource management: The perspective of Malaysian SME owner-managers - Zakaria, Nazlina; Ishak, Khairol Anuar; Arshad, Darwina; Abdullah, Nor Azimah Chew; Ahmad, Norzieiriani (GrowingScience, 2018)
Understanding that the measurement of HRM construct in Small and Medium Enterprises (SMEs) context is relatively critical, this study aims to assess the validity and reliability of HRM measure-ment based on the SME owner-managers’ perspective in the Malaysian context. Following a data collection from 95 SME owner-managers, a confirmatory factor analysis was performed to investigate the factorial validity and reliability of the HRM measurement. The finding indicates that the measurement model was acceptable in consideration of the evidences of adequate reliability, convergent validity and discriminant validity. This study will be beneficial for future researchers, entrepreneurs and policy makers in better understanding to the value of HRM practices towards boosting the SMEs performance.